The antitumor effects of entinostat in ovarian cancer require adaptive immunity. Issue 24 (13th November 2018) - Smith, Haller J.; McCaw, Tyler R.; Londono, Angelina I.; Katre, Ashwini A.; Meza‐Perez, Selene; Yang, Eddy S.; Forero, Andres; Buchsbaum, Donald J.; Randall, Troy D.; Straughn, Jr, J. Michael; Norian, Lyse A.; Arend, Rebecca C.
Abstract : Background: Ovarian cancer is poorly immunogenic; however, increased major histocompatibility complex class II (MHCII) expression correlates with improved immune response and prolonged survival in patients with ovarian cancer. The authors previously demonstrated that the histone deacetylase inhibitor entinostat increases MHCII expression on ovarian cancer cells. In the current study, they evaluated whether entinostat treatment and resultant MHCII expression would enhance beneficial immune responses and impair tumor growth in mice with ovarian cancer. Methods: C57BL/6 mice bearing intraperitoneal ID8 tumors were randomized to receive entinostat 20 mg/kg daily versus control. Changes in messenger RNA (mRNA) expression of 46 genes important for antitumor immunity were evaluated using NanoString analysis, and multicolor flow cytometry was used to measure changes in protein expression and tumor‐infiltrating immune cells. Results: Entinostat treatment decreased the growth of both subcutaneously and omental ID8 tumors and prolonged survival in immunocompetent C57BL/6 mice. NanoString analysis revealed significant changes in mRNA expression in 21 of 46 genes, including increased expression of the MHCI pathway, the MHCII transactivator (CIITA), interferon γ, and granzyme B. C57BL/6 mice that received entinostat had increased MHCII expression on omental tumor cells and a higher frequency of tumor‐infiltrating, CD8‐positive T cells by flow cytometry. In immunocompromised mice, treatment with entinostat had no effect on tumor size and did not increase MHCII expression. Conclusions: In the current murine ovarian cancer model, entinostat treatment enhances beneficial immune responses. Moreover, these antitumor effects of entinostat are dependent on an intact immune system. Future studies combining entinostat with checkpoint inhibitors or other immunomodulatory agents may achieve more durable antitumor responses in patients with ovarian cancer. Abstract : The histone deacetylase inhibitor entinostat increases major histocompatibility complex class II expression, enhances antitumor immune response, and impairs tumor growth in a murine ovarian cancer model. The current findings warrant investigation in more diverse models of immunocompetent murine ovarian cancer as well as patient‐derived models.